A study of the linear transport in single-electron transistor (SET) at differnt temperature using simon 2.0 simulators - 411489 Rabieah Omar; Samsudi Sakrani, supervisor; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2008